2021
DOI: 10.1155/2021/2272469
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Mindfulness and Relaxation on Treatment of Essential Hypertension: Meta-Analysis

Abstract: Background. Some studies published previously have shown a strong correlation between hypertension and psychological nature including impulsion emotion or mindfulness and relaxation temperament, among which mindfulness and relaxation temperament might have a benign influence on blood pressure, ameliorating the hypertension. However, the conclusion was not confirmed. Objective. The meta-analysis was performed to investigate the influence of mindfulness and relaxation on essential hypertension interventions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Метаанализы свидетельствуют о заметном улучшении психологического здоровья и понижении систолического артериального давления (АД) у лиц, страдающих сердечно-сосудистой патологией и практикующих майндфулнес [6]. Показано, что майндфулнес-практики способны существенно понижать как систолическое, так и диастолическое АД [8], и могут быть использованы в комплексном лечении больных с АГ [11,12]. Ещё один систематический обзор показывает, что методы снижения уровня стресса, основанные на майндфулнес, могут быть эффективны при гипертензии, особенно благоприятно влияя на диастолическое АД [13].…”
Section: передовая статья обзоры литературыunclassified
“…Метаанализы свидетельствуют о заметном улучшении психологического здоровья и понижении систолического артериального давления (АД) у лиц, страдающих сердечно-сосудистой патологией и практикующих майндфулнес [6]. Показано, что майндфулнес-практики способны существенно понижать как систолическое, так и диастолическое АД [8], и могут быть использованы в комплексном лечении больных с АГ [11,12]. Ещё один систематический обзор показывает, что методы снижения уровня стресса, основанные на майндфулнес, могут быть эффективны при гипертензии, особенно благоприятно влияя на диастолическое АД [13].…”
Section: передовая статья обзоры литературыunclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%